Selecting Candidates for Liver Transplantation: A Medical Ethics Perspective on the Microallocation of a Scarce and Rationed Resource - Eric M Yoshida (Canadian Journal of Gastroenterology)
Liver transplantation has evolved over the past 35 years from an experimental procedure with high perioperative mortality to an accepted form of treatment with an approximate 85% one-year and 80% three-year patient survival rate. Following the success and acceptance of transplantation in the treatment of end-stage liver disease, there has been a progressive increase in the number of patients seeking a limited supply of donor organs. The ethical focus, on a microallocation level, has therefore changed from that of the 1960s, when the question was whether the procedure should be offered at all, to that of the 1990s and beyond, when the focus is on the proper allocation of a scarce, life-saving resource. The ethical issues concerning fair allocation surrounding liver transplantation are explored, from both the referring physician's perspective and the perspective of the transplant physician. In particular, the contrasting viewpoints of bioethicists Nicholas Rescher and James Childress, with respect to nonmedical and social criteria in the selection of patients for scarce, life-saving therapies, are explored. Lastly, some alternative ethical models for patient selection are reviewed.